Description of a new genus, Galgoria gen. nov. (Hemiptera: Cicadidae: Cicadinae: Leptopsaltriini: Leptopsaltriina) - Lee, Young June (Zootaxa, 2016)
A new cicada genus, Galgoria gen. nov., is described with Tanna herzbergi Schmidt, 1932 (from southern China) as its type species, which is placed in the subtribe Leptopsaltriina Moulton, 1923 of the tribe Leptopsaltriini Moulton, 1923 in the subfamily Cicadinae Latreille, 1802 (Hemiptera: Cicadidae). Tanna herzbergi Schmidt, 1932 is transferred from Tanna Distant, 1905 to Galgoria gen. nov. to become Galgoria herzbergi (Schmidt, 1932) comb. nov. Tanna apicalis Chen, 1940 syn. nov. and Tanna pseudocalis Lei & Chou, 1997 syn. nov. are synonymized here with Galgoria herzbergi (Schmidt, 1932) comb. nov.